Developing cultural awareness through reading literary texts - Wąsikiewicz-Firlej, Emilia (Taikomoji kalbotyra, 2012)
This paper investigates the use of literature in ESL reading classes and its role in developing cultural awareness. The theoretical part focuses on the role of understanding students’ own culture as the fundamental step in developing cultural awareness. Thus, reading literary texts is understood here as text interpretation from native and foreign linguistic and cultural perspectives, defined by Kramsch as “third space”. The study presented in the second part of the paper attempts to verify the effectiveness of Hanauer’s (2001) method of Focus-on-Cultural Understanding in developing cultural awareness, focusing on gender perception, as one of the most fundamental aspects of culture. The study describes 1st year English philology students’ work with selected extracts from the novel Japanland: a year in search of wa by Karin Muller. It aims at identifying students’ perception of gender roles in their own culture and comparing and contrasting them with those dominating in other cultures, namely Japan and the United States. Firstly, students’ attitudes concerning gender roles within their own culture are measured by a pre-questionnaire. Then, after reading the selected extracts and expert’s interpretations, students’ attitudes are investigated again in order to verify the effectiveness of the tested method in cultural awareness education. Despite its limitations, the study showed that the application of Hanauer’s method Focus-on-cultural-understanding increased students’ cultural awareness, especially in respect to gender-related issues, and led to their reflexivity on their own native culture.